ENVIRONMENTAL ISSUES: A GLOBAL CRISIS - Mukul, Shobhika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Today, the world has reached a point where it has obstructed the very source of its development-sustainable growth. Environmental issues have become one of the most critical challenges globally, and sustainable development has stagnated, which is severely affecting the overall progress of life on Earth. If attention is not paid to environmental issues, it may become increasingly difficult for future generations to survive. Problems such as climate change, pollution, and the extinction of plants and animals are continuously escalating. The solution to these issues is only possible through collective efforts. All countries must collaborate and take responsibility for environmental conservation. If we fail to act today, these problems may become even more severe in the future, posing a grave threat to both humanity and the planet.